The craft companion - Barry, Ramona; Jobson, Rebecca (Thames & Hudson, 2016)
Once the domain of the domestic, craft has now infiltrated every creative sphere - including food, fashion, fine art and architecture. If this craft renaissance is indicative of a new wave of keen creatives, then 'The Craft Companion' is the ultimate guide featuring over 30 new and old crafting techniques. Each chapter includes a short historical overview of the craft, with design notes and explanations of key techniques helping beginners to get started. Tools and methods are explored through a combination of hand-drawn illustrations and photography.